(untitled) (ItalianoLinguadue, 2022)
Questo contributo si propone di indagare l’impatto che il corretto o mancato riconoscimento delle funzioni dei meccanismi di coesione testuale ha sul processo di comprensione dei testi funzionali scritti. I risultati restituiti dall’analisi quantitativa e qualitativa dei dati relativi alle prestazioni di studenti e studentesse del biennio della scuola secondaria di secondo grado nelle prove di lettura e comprensione sembrano confermare l’esistenza di una correlazione tra il corretto esito dei questionari di comprensione e la corretta identificazione dei meccanismi di coesione sollecitata negli stessi questionari. Decomposing and recomposing: teaching cohesion to teach understanding This paper aims to investigate the impact that the correct or lack of recognition of the functions of textual cohesion mechanisms has on the process of comprehension of functional written texts. The results obtained through quantitative and qualitative data analysis on the performance of high school students (first and second year) in reading comprehension tests seem to confirm the existence of a correlation between the correct completion of comprehension questionnaires and the correct identification of cohesion mechanisms in the very same questionnaires.